The importance of the Chain of Authority and Ascertaining the Authority in Islam (Salam International Academic Journal, 2011)
This research paper dealt with the fallowing topic: "the importance of attribution in Islam". The research initially specified the linguistic meanings of the words "Sanad" (chain of narrators) and "Isnad" (attribtion).    Then went on to explain the terminological meanings of "Sanad" and "Isnad", and stated the difference between the two terms "Sanad" and "Isnad". Then the paper spoke about the importance of "Sanad" and: Isnad" in Islam in the light of the views of the Muslim scholars. Then the research paper stated that the "Sand" and "Isnad" is one of the characteristics of Muslim Ummah. Then the research paper touched the historical background of "Sanad" in Islam, and stated that it has passed through several stages including the stage of "requiring narrators to mention attribution", then the stage of "commitment of narrators to mention their chain of narrators".    The research paper cited many examples for all of these issues, and at the end of the research paper the results are summarized in order.
Keywords: Isnad; Chains of Transmission; Narrators; Hadith Science; Islam